SOCIETY’S ATTITUDES TOWARD INDONESIA AND PERSPECTIVE IN FACING THE ASEAN ECONOMIC COMMUNITY - Nur Nisai Muslihah (International Conference on Education and Language (ICEL), 2016)
This title of this research is “Society’s Attitudes toward Indonesia and Perspective in Facing the ASEAN Economic Community”. The aims to describe students’ attitude Indonesian and Literature Program STKIP-PGRI Lubuklinggau South Sumatera toward Indonesia and perspective in facing ASEAN Economic Community. Problem of research is why students attitudes of language study program and literature Indonesia ,  STKIP-PGRI Lubuklinggau South Sumatera toward Indonesia and perspective in facing ASEAN Economic Community. The population of research with total number 543 and sample with total number 55 or 10%. Data collection with questionnaire technique. From the data analysis and result research show that students attitudes positive (88,44%) and negative (11,56%) toward Indonesia as international language to communicate in Asean Economic Community, Indonesian is also able to become International language. Considering the potential of Indonesian  intralingua has the fundamental  rule, and extra lingua high number of native speakers. Therefore, the existence  of Asean Economic Community is able to increase the prestige of Indonesian language.